Can Property Taxes Reduce House Price Volatility? : Evidence from U.S. Regions - Poghosyan, Tigran (IMF Working Papers; Working Paper, 2016)
We use a novel dataset on effective property tax rates in U.S. states and metropolitan statistical areas (MSAs) over the 2005-2014 period to analyze the relationship between property tax rates and house price volatility. We find that property tax rates have a negative impact on house price volatility. The impact is causal, with increases in property tax rates leading to a reduction in house price volatility. The results are robust to different measures of house price volatility, estimation methodologies, and additional controls for housing demand and supply. The outcomes of the analysis have important policy implications and suggest that property taxation could be used as an important tool to dampen house price volatility.